Produção dos saberes curriculares nas práticas pedagógicas: pensando a Educação Física nas Escolas de Ensino Fundamental de Vitória (ES) - Silva, Bruno de Oliveira e (2021)
This thesis study is located in the concentration area “Pedagogical and Sociocultural Studies of Physical Education”, in the research line “Physical Education, daily life, curriculum and teacher training” of the Postgraduate Program in Physical Education of the Federal University of Espírito Santo (PPGEF/UFES). Its objective was to problematize, analyze and understand how the relations of knowledge are produced by the subjects in the state curriculum proposal of Espírito Santo (ES) for Physical Education and its pedagogical interventions/practices in the State Schools that have Elementary Education in the city of Vitória/ES. The research was organized in three movements. a) Introductory aspects and Chapter 1: goes back to my story; shows the construction of the object, objective and research questions; rehearses a brief debate on curriculum as language; outlines my investigative paths, based on cultural studies and guided by the Basic Curriculum State School (CBEE) as pedagogical/cultural artifact, in the ten semi-structured interviews (six teachers, two pedagogues, two directors), in the field diary of the Alpha, Beta and Gamma Schools held in the academic year of 2018, and in the cultural analyses of the Circuit of Culture. b) The second movement deals with the operationalization of the Physical Education curricular component and its relations of knowledge. Chapter 2 focuses on prescribed documents that may have curriculum intentions (LDB; DCN; CBEE; PP’s and documents produced by the teachers), seeking to guide an educational and schooling project for the subjects, based on the precepts of the world of work, skills and abilities. In the third chapter, I analyze the prescribed, the said, the seen and the lived knowledge/content, permeated by: the pedagogical and discursive practices; the (im)possibilities of the school routine; and the relations of knowledge. Thus, understand the links of PE with "body culture" and/or “human body culture” and the understandings in the school spacetime about what the curricular component is: i) normalized and bureaucratic; ii) responsible for a certain control of behaviors; iii) salvationist and value-building by itself, instituted in sports and health practices; iv) the component that bothers. c) The last movement analyzes the management, planning, organization and structure of Physical Education in Schools. The fourth chapter subscribes to the conditions between what is expected and desired by the administrative body and what teachers and students think to be possible to accomplished, pointing to different discourses and desires. The last chapter verbalizes about “how” and “who” does Physical Education in the school curriculum, showing that classes are made up of relationships and tensions between institutions, subjects and knowledge that flirt or refute their intervention rituals/practices with pedagogical investments/divestments, according to the micropolitics of negotiations of/in/with the school routine. Finally, it is this set of movements and relationships that define what Physical Education is in each space-time of the schools, transforming this component at times into critical reflections on social, cultural and political elements, at other times in ritualistic activity of occupation of schooled subjects.